Task Technology Fit Adoption in the Recruitment Process Using Google Form for IPSM Members - Muhamad Sigid Safarudin; Yunesman Yunesman; Hermansyah Hermansyah (Universitas Negeri Padang, 2023)
The IT role that is likely to have the greatest effect on human resource processes is that of electronic forms processing transactions. recruitment through this portal is more intended to recruit indirect labor employees or employees who are not directly related to production and with a limited number. Therefore, many companies/organizations use Google Forms for the employee recruitment process which requires a large number of candidates. The purpose of this study is to empirically examine the effect of Task Characteristics, Technology Characteristics, and Individual Characteristics on Task Technology Fit and its influence on Individual Performance, User Satisfaction, Benefit, Utilization, Perceived Ease of Use, and Perceived Usefulness in the recruitment process using the google form. This research is quantitative research that will examine the effect of the variables, namely the independent variable and the dependent variable by testing the hypothesis. The population in this study was 219 members of the Association of Human Resource Practitioners (IPSM). The sample used in this study was 71 respondents who processed data using Smart PLS 3.2.9. The results of this study indicate that 8 of the 9 hypotheses show a significant and positive effect. This shows that IPSM members have adopted Task Technology Fit in their recruitment process by using the Google form. However, it is necessary to conduct further research with more respondents.